KARAKTERISASI KONDISI OPERASI DAN OPTIMASI PROSES PENGOLAHAN AIR LIMBAH INDUSTRI PANGAN - Lintang Zulqaida Fitrahani, Nastiti Siswi Indrasti dan Suprihatin (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT   Increased production in companies will result in the increase the load of the existing wastewater treatment plant. To anticipate the future increase in the COD load, it is in need to characterize dan optimizize the existing wastewater treatment plant. Objectives of this research were characterization of operating conditions, measurement of performance as well as optimization of a food wastewater treatment plant to increase the effluent quality and minimize cost of operating cost.This study was conducted in a food industry in Jakarta. Characterization of the physical installations performed against all operation units that include the unit process physical, biological, and chemical processes. Performance evaluation was carried out using secondary and primary data covering NH4+, phosphate, nitrate, TSS, turbidity, temperature, pH, COD, MLSS, and DO. It was indentified that the biological stage was need to be optimizd especially in the nutrient addition. Almost all units there are differences between condition actual and design that lead to lower efficiencies. It was identified that the optimum nutrition added on Monday was 7 kg/day of urea, 26 kg/day of phosphate as well as 8 kg/day of nutrition liquid. The optimum nutrition added on Thursday was 32 kg/day urea, 45 kg/day phosphate and 8 kg/day nutrition liquid. By implementen these recommendations it can be expected a cost saving by 50%.   Keywords: food industry, nutrient addition, operating conditions, performance optimization